2009
DOI: 10.1097/ajp.0b013e318183cfa4
|View full text |Cite
|
Sign up to set email alerts
|

The Deficit of Pain Inhibition in Fibromyalgia Is More Pronounced in Patients With Comorbid Depressive Symptoms

Abstract: We found that FM+D patients have a more pronounced deficit in pain inhibition as well increased clinical pain. As such, these results show the usefulness of combining psychologic factors and psychophysical measures to identify subgroups of FM patients. These results may have implications for future treatment of FM patients with and without comorbid depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 25 publications
5
61
1
5
Order By: Relevance
“…Pesquisas recentes confirmam a hiperalgesia de pacientes com fibromialgia e apontam o déficit na ação do CIDN. Através do protocolo de somação espacial da dor (45) , Julien et al (46) observam que, ao contrário dos sujeito sadios e de pacientes com lombalgias que demonstram redução da dor após imersão de todo o membro superior em água quente (46) ou fria (47) , nos fibromiálgicos há não há redução significativa da dor, havendo em alguns casos exacerbação desta. Essa ausência de ação dos mecanismos endógenos de controle da dor também tem sido observada em pacientes com cefaleias do tipo tensional (44) .…”
Section: Mecanismos Endógenos De Controle Da Dorunclassified
“…Pesquisas recentes confirmam a hiperalgesia de pacientes com fibromialgia e apontam o déficit na ação do CIDN. Através do protocolo de somação espacial da dor (45) , Julien et al (46) observam que, ao contrário dos sujeito sadios e de pacientes com lombalgias que demonstram redução da dor após imersão de todo o membro superior em água quente (46) ou fria (47) , nos fibromiálgicos há não há redução significativa da dor, havendo em alguns casos exacerbação desta. Essa ausência de ação dos mecanismos endógenos de controle da dor também tem sido observada em pacientes com cefaleias do tipo tensional (44) .…”
Section: Mecanismos Endógenos De Controle Da Dorunclassified
“…12,13 For example, evidence that depressed mood is associated with impaired ''diffuse noxious inhibitory control'' (endogenous inhibition of pain from one noxious stimulus by a second noxious stimulus) illustrates how psychological conditions, such as depression and anxiety, could play a contributory role in the persistence of pain after postsurgical tissue healing. 14 …”
Section: Transition To Chronic Painmentioning
confidence: 99%
“…25,26 Furthermore, mounting evidence suggests that various preoperative factors (e.g., preexisting pain, psychological/psychiatric comorbidities) are associated with a greater risk of persistent postsurgical pain. 14,27 In this context, a genetic disposition for being a high-risk pain responder and at risk for persistent pain is currently receiving much attention. 28,29 At this time, various other techniques with preoperative nociceptive stimulation to predict high-pain responders have been described 30 and may be of future use to allocate high-risk pain patients to more intensive postoperative pain therapy.…”
Section: Perioperative Clinical Assessmentmentioning
confidence: 99%
“…This hypothesis has been demonstrated experimentally in a recent study comparing patients with chronic pain in fibromyalgia with and without depression, which showed that inhibition of pain (via the diffuse noxious inhibitory controls [DNIC]) is further reduced in comorbid depression. 14 Recent studies have highlighted that the central nervous system undergoes long-term plasticity in the presence of chronic pain and depression. The underlying neural circuitry and molecular signalling pathways that underlie this are beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%